EXPRESSION METHODS IN THE SONNETS OF WILLIAM SHAKESPEARE: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article discussess about the existence of unique methods of expression in Shakespeare's sonnets. It is analyzed what symbols the poet widely used in his poems. As a result of the analysis, it was noted that the harmony of form and content is reflected in Shakespeare's sonnets.